Kendali Robot Berdasarkan Perintah Inisialisasi Awal Pengguna - Adit Ilham Nugroho; Mochammad Hannats Hanafi Ichsan; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Over the past 30 years, robotics research and robotics developments continue to evolve, autonomous robots that used to be called traditional industrial robots and animal like or humanoid robots. One of these developments is industrial robot technology or also called industrial robot. There are several reasons why many articulated robots are developed, among others, this robot into the robot factory where the industry is currently growing and also has a free space 360 â€‹â€‹Â°. Industrial robots can improve productivity and efficiency in a factory to run the production line. The author created a protype robot that can move according to the initial initialisation of the user, this robot allows users to run the robot if you want to change the robot movement, compared with existing autonomous robot. This robot is classified as a manual robot that reduces the cost of purchasing a robot. In this study only use Arduino software with EEPROM function to save the movement that has been given. Arduino Software is an open-source software for easy code writing. Arduino hardware device type Mega 2560, Arduino Mega 2560 is a hardware development of Arduino-based microcontroller using ATmega2560 chip to create research prototype. This study uses a total of 5 joints using Servo drives, Servo motors used are Servo SG90. Testing servo movement 0â°-180â° has an average error rate of 1.85% and servo servicing 0â°-360â° has an average error rate of 2.32%. Then in order analysis 1 movement the average value of error is only 2.9% and in the overall command analysis the average error rate is only 1.5%.